2019
DOI: 10.3390/nu11061422
|View full text |Cite
|
Sign up to set email alerts
|

Acute Caffeine Ingestion did not Enhance Punch Performance in Professional Mixed-Martial Arts Athletes

Abstract: Mixed martial arts (MMA) is a combat sport where competitors utilize strikes (punches, kicks, knees, and elbows) and submission techniques to defeat opponents in a cage or ring. The aim of this study was to investigate the effect of acute caffeine ingestion on punching performance by professional MMA athletes. The study used a double-blind, counterbalanced, crossover design. Eleven professional MMA competitors (27.6 ± 4.3 years and 83.5 ± 7.8 kg of body weight) ingested a dose of caffeine (5 mg·kg−1) or placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…Interestingly, caffeine did not have an effect on RTE physical and mental effort when measured in the arm of the experiment examining the acute effects of caffeine. This coincides with previous research [68,72]. Whilst these findings point to physiological mechanisms being the cause of the documented effects, the impact of caffeine on arousal during the exercise as a mechanism cannot be ruled out.…”
Section: Acute Effects Of Caffeine On Muscular Strengthsupporting
confidence: 91%
“…Interestingly, caffeine did not have an effect on RTE physical and mental effort when measured in the arm of the experiment examining the acute effects of caffeine. This coincides with previous research [68,72]. Whilst these findings point to physiological mechanisms being the cause of the documented effects, the impact of caffeine on arousal during the exercise as a mechanism cannot be ruled out.…”
Section: Acute Effects Of Caffeine On Muscular Strengthsupporting
confidence: 91%
“…In combat sports, there is no consensus about CAF effects on physical performances [ 7 ]. In fact, some investigations reported improvements [ 8 , 9 , 10 , 11 ], while others did not [ 12 , 13 ]. This difference could be related to the methodological and the inter-individual variations.…”
Section: Introductionmentioning
confidence: 99%
“…These effects of caffeine have been reported to improve the performance of combat athletes [ 59 ]. Conversely, a study showed no significant effect of caffeine ingestion on punching performance in professional mixed martial arts athletes [ 60 ]. Although genetic analyses were not conducted in this study [ 60 ], genetic factors involved in caffeine metabolism or signaling pathways may significantly affect inter-individual differences in the response to caffeine, similar to that seen for COMT genotype-related DA doses in the CNS [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a study showed no significant effect of caffeine ingestion on punching performance in professional mixed martial arts athletes [ 60 ]. Although genetic analyses were not conducted in this study [ 60 ], genetic factors involved in caffeine metabolism or signaling pathways may significantly affect inter-individual differences in the response to caffeine, similar to that seen for COMT genotype-related DA doses in the CNS [ 50 ]. Consistently, caffeine exhibits different physiological effects dose-dependently, and good responders to caffeine exist [ 59 ].…”
Section: Discussionmentioning
confidence: 99%